The role of microalgae in providing essential minerals for sustainable swine nutrition - Prates, José A. M. (Frontiers in Animal Science, 2025)
The integration of microalgae as a mineral source in swine nutrition provides a sustainable alternative to conventional mineral supplements, offering unique nutritional and environmental benefits. Microalgae species, such as Chlorella vulgaris and Spirulina (currently Limnospira, formerly Arthrospira), are rich in essential minerals, supplying significant levels of calcium (3.5-12.8 g/kg), phosphorus (9.1-16.4 g/kg), zinc (16.2-280 mg/kg) and iron (512-1289 mg/kg), which are critical for growth, bone development and immune support in swine. Inclusion rates of 2-5% in swine diets have demonstrated positive outcomes, with C. vulgaris at 3-5% inclusion levels significantly enhancing bone mineral density and growth in piglets, while Limnospira platensis at 2-3% inclusion has been linked to improved immune responses and increased antibody production. In addition to minerals, microalgae contribute bioactive compounds, n-3 polyunsaturated fatty acids and antioxidants that support swine health and productivity. Environmentally, microalgae offer notable benefits by requiring less land and water compared to conventional crops, effectively sequestering carbon and providing bioremediation capabilities, thereby reducing the ecological impact of livestock production. Despite these advantages, challenges remain in optimizing mineral bioavailability due to the resilient cell walls of certain species, which may require mechanical or enzymatic pre-treatments to enhance nutrient absorption. Future research should aim at improving bioavailability treatments, reducing production costs and conducting long-term feeding trials to validate the economic and health impacts of microalgae in swine diets. Overall, microalgae represent a promising mineral resource for sustainable swine nutrition, aligning with the environmental and economic objectives of modern agriculture.